Genetic diversity of Phytophthora infestans in the Northern Andean region (2011)
Background Phytophthora infestans (Mont.) de Bary, the causal agent of potato late blight, is responsible for tremendous crop losses worldwide. Countries in the northern part of the Andes dedicate a large proportion of the highlands to the production of potato, and more recently, solanaceous fruits such as cape gooseberry (Physalis peruviana) and tree tomato (Solanum betaceum), all of which are hosts of this oomycete. In the Andean region, P. infestans populations have been well characterized in Ecuador and Peru, but are poorly understood in Colombia and Venezuela. To understand the P. infestans population structure in the Northern part of the Andes, four nuclear regions (ITS, Ras, ?-tubulin and Avr3a) and one mitochondrial (Cox1) region were analyzed in isolates of P. infestans sampled from different hosts in Colombia and Venezuela. Results Low genetic diversity was found within this sample of P. infestans isolates from crops within several regions of Colombia and Venezuela, revealing the presence of clonal populations of the pathogen in this region. We detected low frequency heterozygotes, and their distribution patterns might be a consequence of a high migration rate among populations with poor effective gene flow. Consistent genetic differentiation exists among isolates from different regions. Conclusions The results here suggest that in the Northern Andean region P. infestans is a clonal population with some within-clone variation. P. infestans populations in Venezuela reflect historic isolation that is being reinforced by a recent self-sufficiency of potato seeds. In summary, the P. infestans population is mainly shaped by migration and probably by the appearance of variants of key effectors such as Avr3a.